CHALLENGES IN CROSS BORDER ENTREPRENEURSHIP: A CASE STUDY OF MALAY SMES IN MALAYSIA - Masitah Afandi; Ahmad Ridhuwan Abdullah; Siti Som Husin; Mohd Rafi Yaacob (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Cross-border entrepreneurship (CBE) offers small and medium-size enterprises (SME) potential growth, it also entails with crucial challenges that can prevent sustainable international expansion. This study investigates the challenges faced by Malay SMEs in engaging with CBE, focusing on operational management issues, financial constraints, and national policy issues. This study employs a qualitative case study approach, drawing on Cyert and March’s Theory of Firm Behaviour. Sarong (SME 1) and Batik (SME 2) are Malay SME owners who have been engaged in international trade for over three years and represent a broader trend of leveraging traditional cultural products in international markets. The study uncovers a range of issues including poor accounting practices, financial mismanagement, natural disaster disruptions, price objection, limited market visibility, and complex regulatory barriers. It also highlights the critical role of trust in family and international business relationships, as well as the negative impacts of monopolistic practices and overreliance on intermediaries. The findings also reveal that SMEs lack the internal capacity to effectively navigate cross-border trade complexities, and are further constrained by bureaucratic inefficiencies, tax policy confusion, and inadequate access to financial support. These finding shows that Malay SMEs respond to internationalisation challenges through adaptive but irrational decision making shaped by internal routines and external pressures. The study highlighted practical recommendations include streamlining trade regulations, improving tax literacy, strengthening internal business competencies, and promoting inclusive policy frameworks. In short, this study calls for a more supportive ecosystem to enhance the global competitiveness and resilience of Malay SMEs.